Truncal vs Branch Ligation of Inferior Thyroid Arteries in Total Thyroidectomy: Does It Affect Postoperative Hypoparathyroidism?. (April 2021) - Waseem, Talat; Ahmed, Safia Zahir; Baig, Hadia; Ashraf, Muhammad Hasham; Azim, Asad; Azim, Khawaja M.
Objective: Postthyroidectomy hypoparathyroidism remains a significant challenge. Truncal ligation of the inferior thyroid arteries (ITAs) may lead to an increased risk of hypoparathyroidism; however, dissection along the thyroid capsule with branch ligation of the thyroid arteries could be a safer option. This study's objective was to compare the effect of truncal versus branch ligation of the ITAs on the rate of postoperative hypoparathyroidism. Study Design: Randomized prospective trial in line with the CONSORT guidelines. Setting: The study was conducted at a high-volume tertiary care setting. Methods: We randomized 319 patients into 2 groups: truncal ITA ligation (n = 157) and branch ITA ligation (n = 162). The primary outcomes were serum calcium and parathormone levels on the second postoperative day, followed by the levels on months 1, 3, 6, and 12. The need for exogenous replacements was noted. The secondary outcomes, such as operative time, blood loss, and other complications, were also recorded. Results: Our study revealed a significant difference in the incidence of transient hypocalcemia in patients undergoing truncal ITA ligation and branch ITA ligation (22.9% vs 3.1%, P < .05). The results showed that the levels of serum calcium and parathormone dropped on the second postoperative day and that 36 patients from the truncal ITA ligation group required exogenous calcium and vitamin D replacement. In contrast, only 5 patients from the branch ITA ligation group required the same. Conclusions: This is the largest randomized trial of patients undergoing thyroidectomy, and it shows that dissection along the thyroid capsule with branch ligation of the ITAs is more likely to preserve parathyroid function as opposed to truncal ligation of ITAs.